Penerapan Pasal 1320 Kuh Perdata dalam Perjanjian Jual Beli Mystery Box pada Situs E-Commerce Shopee - Rijam Syahfutra; Marnia Rani; Muhammad Fajar Hidayat (Kajian Ilmiah Hukum dan Kenegaraan, 2023)
Purpose: E-commerce is a sale and purchase agreement made through internet media which brings convenience and practicality to carry out buying and selling. One of them is the Shopee e-commerce which offers buying and selling mystery boxes. Mystery box is a sales system in the form of boxes/packages whose contents are not known exactly what goods will be obtained by the buyer.  Methodology: Mystery box buying and selling is carried out on the Shopee e-commerce site by marketing the product without clearly stating the product promised, so the seller only presents the product that the buyer is likely to be able to get at the price that must be paid. What's more, the seller has included a standard clause that the goods that have been received by the buyer cannot be returned or returned. Regarding agreements like this, it is not yet known what goods will become the object of the agreement, so is this mystery box sale and purchase agreement appropriate and reasonable under the law of an agreement through an electronic system and does such a transaction fulfill the legal requirements of an agreement contained in Article 1320 of the Civil Code. The purpose of this study is to find out how the application of Article 1320 of the Civil Code to the mystery box sale and purchase agreement on the Shopee e-commerce site has been fulfilled and the legal consequences for the parties to the mystery box sale and purchase agreement on the Shopee e-commerce site. This research uses a normative legal method with a statutory approach. Results: The results showed that the mystery box sale and purchase agreement on the Shopee e-commerce site did not fulfill the requirements in Article 1320 of the Civil Code, namely subjective requirements and objective requirements. If an agreement is canceled because it does not fulfill the legal requirements of Article 1320 of the Civil Code regarding subjective conditions, the agreement can be canceled and if the objective conditions are not met, the agreement is null and void.